Functional and Character Disparity Are Decoupled in Turtle Mandibles - Jasper Ponstein; Guilherme Hermanson; Merlin W. Jansen; Johan Renaudie; Jörg Fröbisch; Serjoscha W. Evers (Ecology and Evolution)
ABSTRACT Turtles have high shape variation of their mandibles, likely reflecting adaptations to a broad variety of food items and ingestion strategies. Here, we compare functional disparity measured by biomechanical proxies and character disparity measured by discrete morphological characters. Functional and character disparities vary between clades and ecological groups and are thus decoupled. Comparisons with cranial disparity also indicate decoupled patterns within the turtle skull. Exploration of mandibular patterns reveals that several biomechanical configurations or character state combinations can lead to the same feeding type (i.e., convergence) or that high functional disparity can be achieved at a low exhaustion of character state combinations (e.g., cryptodires). Dietary specialists show larger functional disparity than generalists, but the phylogenetically widespread generalist ecology leads to high character disparity signals in the ecotype. Whereas character disparity generally shows high phylogenetic signal, functional disparity patterns correspond to dietary specializations, which may occur convergently across different groups. Despite this, individual functional measurements have overlapping ranges across ecogroups and do not always conform to biomechanical expectations. Jaw opening and closing biomechanical advantages model trade‐offs between force transmission and opening/closing speeds, and turtles show a variety of combinations of values that we try to synthesize into several “jaw types”. Closing mechanical advantage shows that turtles retain high levels of force transmission at the anterior jaw end compared with other groups (e.g., pseudosuchians). This can possibly be explained as an evolutionary adaptation to retain high bite forces at small head sizes.